Deciphering the role of endophytic microbiome in postharvest diseases management of fruits: Opportunity areas in commercial up-scale production - Kumari, Madhuree; Qureshi, Kamal A.; Jaremko, Mariusz; White, James; Singh, Sandeep Kumar; Sharma, Vijay Kumar; Singh, Kshitij Kumar; Santoyo, Gustavo; Puopolo, Gerardo; Kumar, Ajay (Frontiers in Plant Science, 2022)
As the endophytes are widely distributed in the plant's internal compartments, and despite having enormous potential as a biocontrol agent against postharvest diseases of fruits, the fruit-endophyte-pathogen interactions have not been studied detail. Therefore, the review aims to briefly discuss the colonization patterns of endophytes and pathogens in the host tissue, diversity and distribution patterns of endophytes in the carposphere of fruits; host-endophyte-pathogen interactions and the molecular mechanism of the endophytic microbiome in postharvest disease management of fruits. Postharvest loss management is one of the major concerns of the current century. It is considered a critical challenge to food security for the rising global population. However to manage the postharvest loss, still, a large population relies on chemical fungicides, which affect food quality and are hazardous to health and the surrounding environment. However, the scientific community has searched for alternatives for the last two decades. In this context, endophytic microorganisms have emerged as an economical, sustainable and viable option to manage postharvest pathogens with integral colonization properties and eliciting defence response against pathogens. This review extensively summarises the recent developments in the endophytic interactions with harvested fruits and pathogens—the multiple biocontrol traits of endophytes, colonization and diversity patterns of endophytes. In addition, the upscale commercial production of endophytes for postharvest disease treatment.